Fabrication of ZnO-RGO nanorods by electrospinning assisted hydrothermal method with enhanced photocatalytic activity. (June 2019) - Ramos, Pierre G.; Flores, Edson; Luyo, Clemente; Sánchez, Luis A.; Rodriguez, Juan
Highlights: ZnO/RGO seeds were fabricated by electrospinning modified method. ZnO-RGO nanorods growth are influenced by the RGO content on seeds. ZnO-RGO nanorods photocatalytically degraded better methyl orange in water. Abstract: In this study, novel zinc oxide-reduced graphene oxide (ZnO-RGO) nanorods have been fabricated on fluorine-doped tin oxide (FTO) glass substrate by the electrospinning process followed by a hydrothermal technique to grow supported nanorods. The ZnO-RGO precursor seed nanostructured layers were made by calcination of electrospinned nanofibers containing polyvinyl pyrrolidone, zinc acetate and different amounts of RGO at 400 °C for 1 h. Then they were used for hydrothermally growth (ZnO-RGO) Nanorods. The effect of amounts of RGO on the properties of ZnO-RGO NRs was investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), Raman spectroscopy and Photoluminescence (PL). The obtained results evidenced that the coupling of RGO with ZnO improved the photocatalytic activity of ZnO. The ZnO-RGO nanostructure with 1.0 mL of RGO showed the highest photocatalytic activity through degradation of methyl orange (MO) under UV irradiation.